PELAKSANAAN PERKAWINAN PADA MASA PANDEMI COVID – 19 DI KOTA JAYAPURA - Rizky Wisudawan Katjong; Revie Kurnia Katjong (ADISAM PUBLISHER, 2023)
Research under the title 'Implementation of Marriage During the Covid-19 Pandemic in Jayapura City' aims to find out the implementation of marriage during the Covid-19 pandemic in Jayapura City and what obstacles occur in the process of implementing marriage during the pandemic. This study used a juridical approach method and an empirical juridical approach method. A normative juridical approach is the study of the provisions of laws related to the implementation of marriage during the Covid-19 pandemic in Jayapura City. While the empirical juridical approach is an approach to seeing the real nature of law in society. This approach is used to find out and analyze the implementation of normative provisions, especially regarding the implementation of marriage during the Covid-19 pandemic in Jayapura City. Based on the results of the study and discussion, a conclusion can be obtained that the procedure for the implementation of marriage registration during the covid-19 pandemic remains in the lead of PMA No. 20 Year 2019 on marriage registration and the implementation of marriage registration during the covid-19 pandemic have not changed. And in realizing the implementation of marriage during the Covid-19 pandemic, there can be several obstacles. These obstacles include not wearing masks during marriage, not keeping distance or physical distancing, and shaking hands during the marriage process. So it needs to be socialized and tightened marriage requirements during the Covid-19 pandemic in Jayapura City.